Spiritual Communication in Sufi Discourse- A communicative –Semiotic Approach to the Sufi Symbolic Image - الشجيري, سهام; بو الحق, شادلي (ALBAHITH ALALAMI, 2016)
This paper deals with a central issue in the field of human communication and reveals the roaming monitoring of the incitement and hatred speech and violence in media, its language and its methods. In this paper, the researcher seeks to provide a scientific framework for the nature of the discourse of incitement, hatred speech, violence, and the role that media can play in solving conflicts with their different dimensions and in building community peace and preventing the emergence of conflicts among different parties and in different environments. In this paper, the following themes are discussed: The root of the discourse of hatred and incitementThe nature and dimensions of the discourse of incitement and hatred speechThe negative roles of the contents of letters of incitement and hatred speech, hate and violenceLanguage and incitement, hatred and violenceLanguage features in hatred speechHate and incitement speech in the internet